Efek Aktivitas Permainan Bola Basket 3x3Terhadap Perubahan Heart Rate pada Atlet Pelajar Bola Basket SMKN - Hasna Tri Oktavia; Sri Sumartiningsih; Imam Santosa Ciptaning Wahyu W3; Dwi Gansar Santi Wijayanti; Aris Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to determine the effect of 3x3 basketball game activities on changes in heart rate and the intensity zone used after the match. The method used in this study was a quasi-experimental, quantitative method using the One Group Pretest-Posttest Design. The sample in this study was male basketball athletes with an average age of 16.08 ± 0.49 years, weight of 55.9 ± 7.0 kg, height of 1.67 ± 0.05 meters, and a Body Mass Index of 20.13 ± 2.15 in basketball extracurricular SMK Negeri 1 Semarang. The results of this study showed a difference in heart rate before and after the basketball game was played. The effect of increasing significantly occurred by 29.42% of the max heart rate, and the game was in the high-intensity category in zone 4 with a percentage of 80.06%. This increase in heart rate will have an impact on aerobic ability, endurance, and performance in the match. The conclusion shows that the 3x3 basketball game can show a significant increase in heart rate and have an effect on the high-intensity training zone. Keywords: Basketball 3x3, Heart Rate, Intensity, male